2006
DOI: 10.1111/j.1468-4446.2006.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

How secular is Europe?

Abstract: A large body of literature has developed, yielding evidence that religion in general and Churches and Church leaders in particular have lost their once dominant position in contemporary Europe. Evidence is often cited in declining levels of church attendance. Whether Europe should also be qualified as secularized in terms of religious beliefs remains unclear. In this paper we investigate the degree to which European people are secular, focusing not only on religious practices, but also on beliefs. We argue tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(115 citation statements)
references
References 19 publications
4
106
0
5
Order By: Relevance
“…Regarding sociodemographic variables, our findings from Brazilian population are in line with previous findings from other countries (mainly US) indicating that female gender 7,8 and aging are related to higher religious involvement 7,9 . Subjects above 60 years old rated the highest level of religion's importance, but that was not the case for church attendance.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Regarding sociodemographic variables, our findings from Brazilian population are in line with previous findings from other countries (mainly US) indicating that female gender 7,8 and aging are related to higher religious involvement 7,9 . Subjects above 60 years old rated the highest level of religion's importance, but that was not the case for church attendance.…”
supporting
confidence: 82%
“…Several studies performed in the United States (US) have found a positive association between religious involvement with female gender, aging and with AfricanAmerican ethnicity 8,9 . However, there is a scarcity of studies on this issue performed outside the US 7 . It remains unknown if these associations between religiousness with gender, aging and race are also true in other cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be even more the case nowadays, where the process of its decreasing relevance seems still to be ongoing (Halman and Draulans 2006;Koenig and Wolf 2013;Schwinn 2013). However, Weber showed that, at least in the past, a certain religious belief provided a spiritual basis on which modern capitalism could grow.…”
Section: The Protestant Ethic and Capitalismmentioning
confidence: 99%
“…Arts and Halman, 2004;Bréchon, 2004Bréchon, , 2013a or Europe as a whole. Many of these studies of whole Europe have used survey data from the European Values Studies (EVS) (Bréchon, 2013b;Halman, 2003;Halman and Draulans, 2006;Halman and Riis, 2002;Lambert, 2004), and other international databases or surveys (Greeley, 2003;Pickel and Muller, 2009;Pollack, 2008;Pollack, Muller and Pickel, 2012).…”
Section: Introductionmentioning
confidence: 99%